STRUKTUR DAN FUNGSI SASTRA LISAN MASYARAKAT SENGANAN KECAMATAN SEKADAU HILIR KABUPATEN SEKADAU - Firmanda, Gusti Eka; Effendy, Chairil; Priyadi, A. Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ This research was basically the background of the idea to document the oral literature of Senganan Sekadau community. The general problem of this research were the structure and function of oral literature of the people of Senganan Sekadau Hilir Sub-district of Sekadau Regency. There are five titles analyzed, they are Yellow Crocodile, Raja Siak Bulun, Kenyalau Stone, Lawang Kuari, and Lawang Siti. The purpose of this study is to describe the issues discussed, while the benefits of this research that can contribute to the development of oral literature research, especially folklore, can be used as a teaching material in schools, can be used as a reference for further researchers, as well as one of the efforts of cultural preservation especially Senganan Sekadau. The theory used in this research is the theory of oral literature, structural theory, oral literary functions, philology theory, translation theory, learning system planning, and literary learning. This research uses descriptive method, this form of research is qualitative and using structural approach and sociology of literature. Keyword: Structure, Function, Oral Literature, Senganan, SekadauÂ